Dukungan sosial dan grit dengan kesejahteraan subjektif mahasiswa: Menguji peran harga diri sebagai mediator: Social support and grit with subjective well-being of college students: Testing the role of self-esteem as a mediator - Ramandani, Annisa Ayu; Lestari, Sri; Pratisti, Wiwien Dinar (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Students face various challenges that can make them feel depressed, unhappy, and dissatisfied with what they have. The conditions experienced by students reflect their well-being. Low subjective well-being makes students less enthusiastic, anxious, and emotional. This study aims to find empirical evidence of the role of self-esteem as a mediator of social support and grit on subjective well-being. The respondents of this study were 250 active students in Surakarta City recruited using cluster sampling. Data collection used four scales: Subjective Well-being Scale, Self-Esteem Scale, Social Support Scale, and Grit Scale. The Structural Equation Model program, with the help of the Jamovi application, was used for data analysis. The measurement model of each variable meets the standard values ​​of NFI, TLI, RMSEA, and SRMR, so it is said to be a good fit. The results of this study confirm the importance of social support and grit in increasing students’ self-esteem and subsequently increasing their subjective well-being.